Who says it's a man's world : the girls' guide to corporate domination - Bennington, Emily (American Management Association, 2013)
Women are primed to level the corporate playing field. What does this mean for you? Absolutely nothing, if you don't know how to earn the respect and credibility it takes to see real traction in your career. In this book you'll find specific actions and answers you need to enter the executive suite, including: measurable steps you can take to enhance your reputation in five key areas: self-awareness, social skills, personal effectiveness, team building, and leadership; eye-opening assessments that will help you identify your most effective actions, map out your personal career plan, and gauge your own promotability; career-planning templates, worksheets, and tools for applying the book's lessons; first-person narratives detailing lessons hard-learned by highly successful women executives; "how to handle it" sections that give you step-by-step guidelines for navigating tricky situations. With this no-nonsense approach, you'll not only learn how to "play the game" at work but how to win it on your own terms.--From publisher description.